2015
DOI: 10.3791/52427
|View full text |Cite
|
Sign up to set email alerts
|

Functional Reconstitution and Channel Activity Measurements of Purified Wildtype and Mutant CFTR Protein

Abstract: The Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) is a unique channel-forming member of the ATP Binding Cassette (ABC) superfamily of transporters. The phosphorylation and nucleotide dependent chloride channel activity of CFTR has been frequently studied in whole cell systems and as single channels in excised membrane patches. Many Cystic Fibrosis-causing mutations have been shown to alter this activity. While a small number of purification protocols have been published, a fast reconstitution meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…1 A ). In a subset of our experiments, we confirmed that the purified full-length WT-CFTR is functional as a phosphorylation and ATP-regulated anion channel upon reconstitution in proteoliposomes using our previously published iodide efflux protocols ( 12 , 14 ).…”
Section: Resultssupporting
confidence: 72%
“…1 A ). In a subset of our experiments, we confirmed that the purified full-length WT-CFTR is functional as a phosphorylation and ATP-regulated anion channel upon reconstitution in proteoliposomes using our previously published iodide efflux protocols ( 12 , 14 ).…”
Section: Resultssupporting
confidence: 72%
“…Each preparation was separately reconstituted into pre-formed 1,2-palmitoyl-oleoyl-sn-glycero-3-phosphocholine (POPC) liposomes. The anion electrodiffusion from liposomes normalized for the amount of CFTR inserted into liposomes were measured (Refer to CFTR quantification section in Materials and Methods for more details on the method) in order to determine the relative proportion of channel competent CFTR molecules from the two preparations [40,41]. Briefly, in this assay, CFTR protein in amphipols or LMNG micelles was reconstituted into POPC proteoliposomes with equal concentrations of potassium iodide inside and potassium glutamate outside of the liposomes to provide a driving force for iodide efflux and to maintain the osmolarity [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…The anion electrodiffusion from liposomes normalized for the amount of CFTR inserted into liposomes were measured (Refer to CFTR quantification section in Materials and Methods for more details on the method) in order to determine the relative proportion of channel competent CFTR molecules from the two preparations [40,41]. Briefly, in this assay, CFTR protein in amphipols or LMNG micelles was reconstituted into POPC proteoliposomes with equal concentrations of potassium iodide inside and potassium glutamate outside of the liposomes to provide a driving force for iodide efflux and to maintain the osmolarity [40,41]. The addition of valinomycin, an ionophore that selectively facilitates potassium ion flux out of the proteoliposomes, alleviates the charge build up in the proteoliposomes and allows for iodide efflux through activated CFTR [40,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this spirit, a recent report described the extraction of CFTR from insect cell membranes using a zwitterionic detergent foscholine-14 followed by rapid exchange into the non-ionic detergent dodecylmaltoside (DDM) [41]. Following this protocol, the authors measured channel flux and reconstituted ATPase activity.…”
Section: Purification Of Cftrmentioning
confidence: 99%